Leaders or readers, whom to please? News values in the transition of the Chinese press. (September 2016) - Huan, Changpeng
Abstract: This paper takes news values as the analytical point of entry to understand the working of Chinese press in the wake of its marketization reform. The reform has resulted Chinese newspapers in facing an increasingly tightening tension between the political power of the government and economic forces of the market. Drawing on four different but complementary datasets – news policy documents, media editorial meetings, interviews with Chinese journalism practitioners and a newly constructed corpus of Chinese news reporting, this study found that maneuvering news values concerning different news actors and events constituted a distinctive way for Chinese journalism practitioners to circumvent the dilemma. To please leaders, the news values of Eliteness and Positivity were foregrounded, while to please readers, the news values of Personalization and Negativity were highlighted. The findings are important for understanding Chinese journalists' mindsets to accommodate structural changes of Chinese press in journalistic practices. Highlights: This paper adopts a wide range of data to examine news values in Chinese press, including policy documents, interviews with Chinese journalism practitioners, observation of editorial meetings and a corpus of news texts. this paper advances a position that the enactment of news values is a nexus of practice, and thus this study integrates social, cognitive and discursive aspects of news values. this paper finds that Chinese journalism practitioners practice news values of Eliteness and Positivity to please political leaders, while practice values of Personalization and Negativity to please readers. this papers argues that Chinese journalism practitioners maneuver different news values to please readers and leaders at the same time in order to maintain political and economic safety.